DETERMINANTS OF REVISIT INTENTION (A SYSTEMATIC LYTERATURE REVIEW) - Isnia, Aulia N.; Qomariah, Nurul (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective This systematic literature review (SLR) explores the determinants influencing revisit intention in various contexts, particularly in tourism and hospitality. Revisit intention, a critical indicator of customer loyalty, determines the likelihood of a customer returning to a destination or service. Understanding its determinants is vital for improving customer retention strategies and enhancing service offerings. This study aims to identify recurring themes and novel determinants shaping revisit intention. Method: Articles were selected through a systematic search on ScienceDirect using the keywords “determinants of revisit intention.” A total of 30 peer-reviewed articles published between 2016 and 2025 were included. A descriptive approach was employed to synthesize findings, categorizing the determinants into thematic clusters. Results: The review identified critical determinants such as customer satisfaction, destination image, perceived value, and service quality. Emerging factors, including technological integration and sustainability, also play significant roles in shaping revisit intentions. Novelty: This study provides a comprehensive synthesis of recent developments in revisit intention research, offering theoretical and managerial implications for improving consumer retention strategies.